(untitled) (Journal of Health, Population and Nutrition, 2010)
A 12-year old girl was brought to the Dhaka Hospital of ICDDR,B with diarrhoea. Incidentally, the parents provided a history of repeated episodes of pallor and jaundice since she was two and half years old. Three of her family members had similar problems. History, clinical examination, and laboratory findings of the girl and her family members suggested a case of hereditary spherocytosis. To our knowledge, this is the first report of such a case in Bangladesh. Key words: Anaemia; Anaemia, Haemolytic; Spherocytosis, Hereditary; Bangladesh DOI: 10.3329/jhpn.v28i1.4529 J Health Popul Nutr 2010 Feb; 28(1): 107-109